Romantisme Muh. Rustandi Kartakusuma Dalam Karya Sastra Sunda - Isnendes, Chye Retty; Julianingrum, Anisa (Metta : Jurnal Ilmu Multidisiplin, 2025)
Love genre novels are one of the novels that are liked by many people, especially if written by famous authors whose reputations are known nationally. Among the famous authors is Muh. Rustandi Kartakusumah, he was an author, playwright, film scriptwriter, essayist, and Indonesian literary critic in his time. Not many people know that he was also a short story writer and novelist in Sundanese. His love stories, both in Indonesian literature and in Sundanese literature, are full of tendencies, but also romantic. This romance that is full of commitment is interesting to study. Thus, the purpose of this paper is to analyze the romanticism of Muh. Rustandi Kartakusumah in three Sundanese literary works. The research method is descriptive analysis with a literature review technique. The romanticism of Muh. Rustandi Kartakusumah is traced in the romantic aspect of his two Sundanese novels and one short story. The romantic aspect contained in Muh. Rustandi Kartakusuma's Sundanese literary works is related to the elements of a love triangle and types of love. The elements of a love triangle are intimacy, passion, and commitment. The types are: love is like an addiction, love is like art, love is like a game, love is like a garden (must be cared for), love is belief, and love is sacrifice.